Effect of Temperature on Recrystallization Annealing Behavior of Drawn AZ31 Magnesium Alloy Wire - FANG Wen bin; WANG Dong wei; Zhang Xu dong; WANG Xin; LI Xue wen (Journal of Harbin University of Science and Technology)
In this paper, the tensile state AZ31 magnesium alloy wire with diameter of 13mm and deformation degree of 25% was used as raw material to study the influence of temperature on recrystallization annealing behavior of wire The results show that after annealing at 200℃, the microstructure consists of fine recrystallized grains and coarsely deformed grains When the annealing temperature is 250℃ and above, complete recrystallized structure is formed With the increase of annealing temperature, small size recrystallization, the number of grains increases first and then decreases, and the average grain size decreases first and then increases When the temperature increases to 250℃ and above, the grain size distribution changes from bimodal to unimodal, and the number of fine particles per unit area significanly decreases, and the peak of the grain size distribution increases continuously to the right The wire recrystallization process is divided into three typical stages: fine equiaxed crystal formation, fine crystal growth and grain uniformization